INNOVATION IN MUSIC FUSION MUSIC: संगीत में नवाचार फ्यूज़न म्यूजिक - Masurkar, Shilpa (International Journal of Research -GRANTHAALAYAH, 2015)
The country of India is considered a symbol of art and culture. Indian music has been in the highest position since time immemorial as an invaluable heritage of our India. Music must have come into existence at the same time as the creation of the creation, it is believed that, but if we look at the music, the music resides in the nature, the currents of rivers, the sound of tomorrow, the sound of wind. Music can also be seen, heard, understood and felt in the sound of the wind hitting the leaves and the sound of the drops of rain falling on the leaves, birds chirping etc. Music is the only means of religion, meaning, work and salvation. भारत देश कला व संस्कृति का प्रतीक माना जाता है। भारतीय संगीत हमारे भारत की अमूल्य धरोहर के रूप में अति प्राचीन काल से ही सर्वोच्च स्थान पर विद्यमान है। सृष्टि की उत्पत्ति के साथ ही संगीत भी अस्तित्व में आया होगा, ऐसा माना गया है, परंतु देखा जाये तो प्रकृति के रोम-रोम में ही संगीत बसता है, नदियों की बहती धारा, कल-कल की ध्वनि, हवा की सन्-सन् ध्वनि, पत्तों से टकराती हवा की ध्वनि व पत्तों पर गिरती बारिश के बूंदों के टप्-टप् की ध्वनि, पक्षियों की चहचहाट आदि में संगीत को देखा, सुना, समझा व महसूस भी किया जा सकता है। संगीत ही धर्म, अर्थ, काम और मोक्ष का एकमात्र साधन है।